Increasing the compact density and its consistency in the cross-section for enhancing the anti-corrosion and mechanical properties of micro-arc oxidation coatings - Ke Wang; Sujuan Wu; Yadong Huang; Ran Wen; Yanning Chen; Daiqi Zhou; Liang Wu; Jiangfeng Song; Zhihua Dong; Bin Jiang (Journal of Materials Research and Technology, 2022)
The micro-arc oxidation coatings (MAO) coatings formed on the magnesium (Mg) matrix usually have various porosity in the cross-section due to the uneven thermal stress, resulting in the non-consistent compact density in the external and inner layer. However, the consistency of the compact density in the cross-section is less concerned, and its effect on the surficial anti-corrosion and mechanical properties is still unclear. Herein, we employed the Zirconium Oxide particles as a heat-absorbing agent to tune the temperature gradient and achieved the in situ growth of MAO coatings on Mg alloy with a tunable compact density in the external layer and inner layer separately. It is found that compact density plays a key role in corrosion resistance, while the consistency of compact density along the cross-section is very crucial for the mechanical properties. Increasing the compact density and reducing its gradual difference could significantly enhance both the anti-corrosion and mechanical properties. The effect of the inconsistent compact density on the anti-corrosion property could be weakened by reducing the porosity on the external layer, but the simulation results demonstrate its effect on the mechanical properties would be strengthened due to the stress concentration. MAO coatings with homogeneous and compact structures in the cross-section present superior anti-corrosion properties and excellent mechanical properties.